Model based control of the heat exchanger system with accumulative heat reservoir - Ahpichitpongchai, Panuwat; Kamonwattana, Kamonchanok; Intarit, Wiriya; Wongvanich, Napasool; Kongratana, Viriya (My University, 2019)
This paper designs a model based control system for the heat exchanger system with accumulative heat reservoir. The heat exchanger system was firstly modelled through the set of five differential equations, that also take into account the heat accumulation inside the reservoirs. Temperature data was obtained through the use of a temperature sensor (LM 35) which is connected to LabView through a DAQ. The collected data was then processed using an integral based method to determine the parameters of the heat exchanger system. The appropriate PID gains are selected by pole placement methodology. Results show that the set of PID gains that were determined through the use of calculations outperformed the arbitrary chosen set of gains.
Keywords: accumulating heat; heat exchanger; PID controller; Simplified Modelling